ChemInform Abstract: Crystal Structures of the Calcium Pump and Sarcolipin in the Mg2+‐Bound E1 State. Issue 21 (2nd May 2013) - Toyoshima, Chikashi; Iwasawa, Shiho; Ogawa, Haruo; Hirata, Ayami; Tsueda, Junko; Inesi, Giuseppe
Abstract Review: 42 refs.